Injustiça na escola: representações sociais de alunos do ensino fundamental e médio - Carbone, Renata Aparecida [UNESP]; Menin, Maria Suzana De Stéfano [UNESP] (Faculdade de Educação da Universidade de São Paulo, 2004)
This article reports on two studies that aimed at the investigation of how students from elementary and secondary schools, both private and public, from the town of Presidente Prudente (SP) represent situations of injustice at school, as well as their agents and the kind of actions they take. Two sets of data were analyzed: 1) open answers to a questionnaire submitted in 1999 to 480 pupils from the 8th grade of the elementary school and the 1st grade of secondary school; the answers selected were those in which reference was made to injustice at school; 2) answers given in 2003 by students of the 5th grade of the elementary school to questions about injustice at school. The theoretical analysis was based on the approach of the Psychology of Moral Development of Piaget and Kohlberg, and on the Social Representation approach created by Moscovici. Comparing the 1999 and the 2003 studies the conclusions can be drawn that none of the school series see the school as a just community, and that retributive and legal injustices prevail. The main agents of injustice are revealed to be teachers (against students), followed by students (against other students). Students from private schools point the teachers as the agents of injustice more often that students from public schools. The latter put first the injustices among students; they also opposed more strongly the rules that go against personal needs than their counterparts from private schools.

Neste artigo apresenta-se o relato sobre duas pesquisas que buscaram investigar como os alunos do ensino fundamental e médio de escolas públicas e particulares do município de Presidente Prudente representam situações de injustiça na escola, bem como seus agentes e os tipos de ações que cometem. Dois conjuntos de dados foram analisados: 1) respostas obtidas por meio de questões abertas incluídas num questionário aplicado em 480 alunos em 1999, em alunos da 8ª série do ensino fundamental e 1ª série do ensino médio, nas quais foram selecionadas, para análise, as respostas que tivessem a escola como local de injustiça; 2) respostas de alunos da 5ª. série do ensino fundamental em questões sobre injustiça na escola aplicadas em 2003. Para análise teórica, foram utilizadas as abordagens da Psicologia do Desenvolvimento Moral de Piaget e Kohlberg e da Representação Social, criada por Moscovici. Comparando as duas pesquisas, a de 1999 e a de 2003, conclui-se que em nenhuma das séries a escola aparece como uma comunidade justa e que prevalecem os casos de injustiça retributiva e legal. Como principais agentes de injustiças aparecem, primeiramente, o professor perante seus alunos e, em segundo lugar, os alunos entre eles mesmos. Os alunos de escola particular apontaram mais o professor como agente de injustiças que os de escola pública. Entre esses as injustiças entre alunos foi mais citada. Os alunos de escola pública se posicionaram contra regras escolares que se opõem às necessidades pessoais com mais veemência que os de escola particular.
Injustice at school: social representations of elementary and secondary school students
Keywords: Social psychology; Justice; School; Psicologia Social; Justiça; Escola